Bandpass filter design using microstrip split-ring rectangular resonator / Noor Iza Zamran - Zamran, Noor Iza (2011)
In this thesis, a multilayer bandpass filter using microstrip split-ring resonator has been proposed for frequency range of 1.452 GHz to 1.492 GHz. The filter was designed using Computer Simulation Technology (CST) software and implement on Rogers Duroid RO3003 substrate with dielectric constant, 8r of 3 and tan 8 of 0.0013 with thickness 0.75 mm. The insertion loss and return loss for this filter is -0.4539dB and -23.93 dB, respectively. The effect of coupling gap of the split-ring resonator and few other parameters was studied and the analysis has been included.